KORELASI KETERAMPILAN MENYIMAK TEKS DESKRIPSI TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 2 BAYANG - Ramanda, Aria Nada; Emidar, Emidar; Asri, Yasnur (Universitas Negeri Padang, 2018)
ABSTRACT This article was to (1) describe the level of listening comprehension skills of the text description of the seventh grade students of SMP Negeri 2 Bayang (2) to describe the skill level of writing the description text of the seventh grade students of SMP Negeri 2 Bayang; and (3) to describe the correlational of listening comprehension skills of the description text skill of writing text description of student of class VII of SMP Negeri 2 Bayang. Theories used in this research are skill, listening comprehension of description text, writing skill of description, correlation skill listening comprehension text description to skill of writing text description of student class VII SMP Negeri 2 Bayang.This research type is quantitative research by using descriptive method. An descriptive method with correlation approach. The population in this study is the students of class VII of SMP Negeri 2 Bayang registered in the academic year 2017/2018 which amounted to 218 students. The sample of this study amounted to 40 students. The sampling of this research was done by propotional random sampling technique. The data of this research is score of skill listening comprehension result in the form of objective test and score of skill writing skill in the form of performance test of class VII student of SMP Negeri 2 Bayang. Based on the research result. It is also evident in the implementation of learning that shows the interrelationship between one another. Kata kunci: Keterampilan Menyimak; Keterampilan